Reflections on the production of gestures in foreign language students - López-Ozieblo, Renia (Didáctica. Lengua y Literatura, 2016)
In foreign language teaching and evaluation little, if any, consideration is given to gestures, that is, to hand movements performed together with speech. However, in recent decades various gesture production models have been suggested, models that should be considered in the foreign language classroom. Some researchers propose the existence of two more or less independent parallel processes, one for gesture, one for speech, while others suggest a unity of the two modalities, the Growth Point. This article summarises existing theories in gesture-speech processing and it illustrates it with the results of a study on gesture production by native speakers and learners, in a formal context, of English and Spanish. It was observed that, depending on the level of proficiency, gestures with iconicity (those related to the content of the speech) or of a pragmatic nature (those used to emphasize or maintain the rhythm of speech) differed. These results suggest the existence of two systems of gesture-speech processing: one where the gesture and speech are produced separately and another where they are a unit. Understanding these differences and processes can be helpful in the foreign language classroom to facilitate students’ oral production and for teachers to evaluate proficiency levels in the foreign language.
Keywords: Gestures; speech-gesture processing; native and foreign language speakers.